Pembinaan Prestasi Atlet Pencak Silat di Kabupaten Pemalang - Yahya Mughni Labib; Ipang Setiawan (Universitas Negeri Semarang, 2023)
The purpose of this study was to find out about the achievement of pencak silat athletes in Pemalang Regency. This study uses a descriptive approach with data collection using the method of Observation, Interview and Documentation. This research was conducted in Pemalang Regency. The data techniques used were data triangulation, data analysis, data reduction, data presentation and conclusion analysis. The results of the study show that massing is carried out during the new school year through extracurricular schools, media and educational institutions, carried out by standing as a benchmark for athletes, achievement strategies that are applied with special training, training is carried out with separate conditions, training programs are made but not written, Existing facilities still need to be added, the existing funds for IPSI are obtained from KONI sponsors and college fees under the auspices of IPSI while for colleges it comes from member fees and schools that have pencak silat colleges under IPSI, the organization is managed by the elected college administrators. The conclusion is that the implementation of pencak silat achievement development in Pemalang Regency is not going well or not optimally. Suggestions, Pemalang Regency pencak silat to pay more attention to the ongoing coaching process in order to achieve maximum, for Pemalang Regency pencak silat administrators to add more existing facilities to facilitate the athlete coaching process